Japanese Corporate Strategies to Achieve International Competitiveness: A Case of The Telecom Industry - Kiranakumar Momaya,; D.K. Banwet Ajitabh,; Himanshu Shee, (Asian Academy of Management Journal, 2001)
Japan, a competitiveness leader, for most of the 1970s and 1980s is at the crossroads. Most of the 1990s, it remained in recession, and there are serious doubts about the competitiveness of Japan and its leading industries. Telecom is a vital infrastructure industry for emerging e-lance economy. An attempt was made to evaluate the competitive performance of the Japanese telecom industry in an Asian context . The strategies of Japanese firms to enhance their and their industry's competitiveness are also briefly examined. The findings of an attempt to evaluate relative competitiveness at the industry level in the context of the telecom industry in India, Japan and Korea are presented here. Competitive analysis of the industry in three countries is done using the Porter's Diamond model. Detailed evaluation is performed using an adaptation of Asset- Process-Performance model. Then, an attempt is made to understand the role of corporate strategy in the remarkable success of the Japanese industry. The strategies of Korean firms and Indian firms are also compared briefly. Finally, conclusions are drawn based on findings of the research.